(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article reveals the purpose of the policy carried out in the field of physical education and sports during the years of the former Soviet power on the example of the Navoi region. Volunteer sports societies formed during the former Union period and their activities, the state of the sports, the competitions held and their results are highlighted.